On the stress distribution in a prestretched simply supported strip containing two neighboring circular holes under forced vibration - Yahnioglu, N. (SPRINGER, 2007)
The three-dimensional linearized theory of elastic waves in initially stressed bodies under plane strain is used to study the influence of the initial stretching of a simply supported plate strip with two neighboring circular holes on the stress concentration around the holes caused by additional uniformly distributed dynamic (time-harmonic) normal forces acting on the upper face. The corresponding problem is formulated and solved by the finite-element method. Numerical results on the stress concentration around the holes and the influence of the initial stretching on this concentration are presented.
Keywords: dynamic (time-harmonic) stress field; initial stresses; plate strip; forced vibration; CYLINDRICAL-SHELLS; SPHERICAL-SHELLS; DEFORMATION; STATE; Mechanics